MÉTRICAS DE COMPORTAMIENTO Y SENTIMIENTOS PARA LA GESTIÓN Y PRODUCCIÓN DE CONTENIDOS AUDIOVISUALES - Dra. GUADALUPE AGUADO GUADALUPE,Dr. ALBERTO LUIS GARCÍA GARCÍA (Fonseca, Journal of Communication, 2023)
This article analyzes the chief behavior and emotion metrics employed in the digital environment along with their impact on the management and production of audiovisual content. The objectives are: 1) to identify the metrics and indicators employed for detecting consumer experiences and emotions; 2) to categorize the indicators used; and 3) to observe the extent to which said indicators affect content management and production. For this purpose, the main measuring tools were chosen, the indicators used for each of them were identified, their contribution was evaluated, and they were catalogued according to the services they provide. The conclusion reached is that behavior and emotion metrics provide a new way of understanding the capacity of contents to influence users and viewers, impacting on essential aspects when producing contents with a certain degree of success prediction.